Clinicopathologic evaluation of mammary Paget′s disease - Meibodi Naser; Ghoyunlu Vahid; Javidi Zari; Nahidi Yalda (Wolters Kluwer Medknow Publications, 2008)
Mammary and extramammary Paget′s diseases are rare neoplasms of epidermis and mucosal epithelium. Due to their nonspecific and variable clinical view, they have differential diagnosis with eczema, melanoma, Bowen′s disease, etc. To the best of our knowledge, no such study has been performed in Iran regarding the prevalence, clinical aspects, underlying disease and pathological characteristics of these two diseases. In this study, we have evaluated the clinical and histopathological aspects of this disorder. Materials and Methods: In this retrospective study, all Paget′s biopsied samples referred to the Pathology Department of Imam-Reza hospital, Mashhad, since 1984 till 2004 were evaluated. Collected data were analyzed by descriptive statistical methods. Results: Among 98925 specimens, there were 29 cases of Paget′s disease. All cases were married women suffering from mammary Paget. The mean age was 53 ± 11 years. Left and right breast involvement was observed in 17 and 12 cases, all unilateral. The most common clinical view was ulcerated (27%) and then erythematosus exudative plaques. More than 50% of patients were symptomatic. Most common symptoms were itching, pain and burning. The exclusive underlying pathological diagnosis was ductal carcinoma (55%). Discussion: In most cases, the clinical view of mammary Paget′s disease was helpful. Unilateral ulcerated plaque was the most common clinical sign. Majority of the accompanying pathology was ductal carcinoma. We had no cases of extramammary Paget′s disease in our study.